Implementasi Pembelajaran Berbasis Kecerdasan Majemuk dalam Meningkatkan Motivasi dan Hasil Belajar Kognitif Fiqih - Ana Syifaunajah; Ahmad Syaeful Rahman; Fajar Meihadi (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2020)
This study explains the effect of multiple intelligence learning in increasing motivation and learning outcomes of fiqh. The research approach used quantitative research with data collection using interview and questionnaire techniques. The results of this study: the implementation of multiple intelligence-based learning in fiqih subjects in class VIII B was appropriate, while the implementation in class VII c was not optimal, the difference in learning motivation from the pretest results of the experimental class students' motivation was 53.41 and the control class motivation was as large as 51.60 is in the medium category. Meanwhile, after the posttest there was an increase in the initial expression class 51.41 to 81.03 in the high category, while the control class initially 51.60 to 65.20 in the medium category. That there is a difference in learning motivation between the experimental class and the control class. The increase in experimental cognitive learning outcomes was 0.72 in the high category, while the control class was 0.34 in the moderate category. The response of students to multiple intelligence-based learning is good with an average value of 74.11 in the interval 60 - 79.99 which includes good qualifications. Abstrak Penelitian ini menjelaskan pengaruh pembelajaran dengan kecerdasan majemuk dalam meningkatkan motivasi dan hasil belajar fiqih. Pendekatan penelitian menggunakan penelitian kuantatif dengan pengumpulan data menggunakan teknik wawancara dan angket. Adapun hasil penelitian ini: implementasi pembelajaran berbasis kecerdasan majemuk pada mata pelajaran fiqih di kelas VIII B sudah sesuai, sedangkan pelaksanaan di kelas VII c belum optimal, perbedaan motivasi belajar dari hasil pretest motivasi peserta didik kelas eksperimen sebesar 53,41 dan motivasi kelas kontrol sebsesar 51,60 berada dalam katagori sedang. Sedangkan setelah posttest mengalami peningkatan yaitu kelas ekspremen awalnya 51,41 menjadi 81,03 berkatagori tinggi sedangkan kelas kontrol awalnya 51,60 menjdi 65,20 dalam katagori sedang. Terdapat perbedaan motivasi belajar antara kelas eksperimen dan kelas kontrol. Peningkatan hasil belajar kognitif eksperimen sebesar 0,72 dengan katagori tinggi, sedangkan kelas kontrol sebesar 0,34 berkatagori sedang. Tanggapan peserta didik terhadap pembelajaran berbasis kecerdasan majemuk yaitu baik dengan nilai rata-rata 74,11 berada pada interval 60 – 79,99 yang termasuk pada kualifikasi baik.